(Post-)Migration in the age of globalisation: new challenges to imagination and representation. Issue 2 (21st August 2017) - Petersen, Anne Ring; Schramm, Moritz
ABSTRACT: In their introduction to this special issue, the editors first outline the overall thematic content of the issue. The editors suggest that art, culture, and aesthetics have an important role to play with respect to the intensified migration and globalisation that characterise the world today, because globalisation and migration present new and encompassing challenges to imagination and representation, as well as challenging the creation of images (in a broad sense), which is so essential to both individual and collective worldmaking. They move on to present two historical examples from Britain and Germany, respectively, in order to establish a pre-history of the contemporary conditions and developments. After discussing some of the key concepts and theoretical discourses central to the theme and the articles of this special issue of Journal of Aesthetics & Culture —migration, postmigration, multiculturalism, cosmopolitanism, worldmaking and belonging—they conclude with brief introductions to the individual contributions.